Enzyme Immunoassay for the Detection of Human Chorionic Gonadotropin (HCG) and Placental MRNA Marker a Practical Technique for Forensic Pregnancy Identification in Bloodstains - Sheeba Shabbir, Nusrat Ali, Iftikhar Ahmad, Aina Khurshid, Muhammad Farhan Siddiq Rao, Sabika Hussain, Muhammad Rizwan (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: The diagnosis of pregnancy from forensic bloodstains can be useful in cases of infanticide, criminal abortions and missing person identification. Objective: This research illustrated the use of a rapid, precise, and tremendously responsive enzyme immunoassay kit designed for medical usage, which is put to good use in our lab for qualitative HCG detection in blood stains and has proven to be a useful tool in forensic pregnancy identification. Methods: HCG concentrations had previously been generally known, and total eighty whole blood samples were taken: forty expectant females (every single one between months one to six of pregnancy), twenty healthy young males, and twenty postmenopausal females with good health ration has been cleared in all data. Results: Enzyme immunoassay is a useful forensic technique for detecting human chorionic gonadotropin hormone in pregnant women. In the forty sample batch that was dated for six months, 37 samples (92.5%) yielded positive results, 38 of which (95%) yielded good outcomes in the qualitative analysis, most of them within the sensitivities boundary. The samples that were diluted to 1/100 and 1/200 and kept at room temperature for one week and six months period, respectively, produced just two (5.0%) and five (12.5%) successful results and the samples showed negative results when diluted to 1/200 and stored for six months. Practical implication This paper reports on human chorionic gonadotropin (HCG) detection in bloodstains based on enzyme immunoassay. Conclusion: Enzyme immunoassay has proven to be a suitable method intended for detecting an hCG hormone in blood stains, allowing for the qualitative assessment of hCG, and making it particularly interesting for use in forensic science applications. Keywords: Enzyme immunoassay, human chorionic gonadotropin (hCG), pregnancy, bloodstain